Case report: Image guidance retrieval of a foreign body in retropharyngeal space - Wu, Xingmei; Wang, Yongquan; Sun, Wei; Zhu, Xiaolin (Frontiers in Surgery, 2022)
Background: Ingested foreign bodies fully embedded in retropharyngeal space present a unique challenge, as they can be difficult to locate and visualize via classic transoral laryngoscopy or transcervical approach. Methods: We retrieved a complete extraluminal chicken bone located in patient’s retropharyngeal space at the level of C4-C5 spine through a well-designed transcervical approach with combination of image-guided neck navigation. Conclusion: Combination use of image-guided neck navigation and dedicated transcervical approach for location of foreign body in retropharyngeal space is practical and available for clinical application.